Kebudayaan Indonesia: Mengenal Lebih Dekat Debus, Atraksi Menantang Maut - azzahra, novia fatma (Maliki Interdisciplinary Journal, 2025)
Indonesian culture is the result of the heritage of this diversity. One of the unique performing arts is Indonesian martial arts or better known as Debus art. This art is known for its toughness in deadly attractions. In the art, there is physical strength, courage, and spirituality shown in an interesting exhibition. By performing various actions of the Debus performer, Debus artists try to expose the nation's culture with its courageous values. Debus art is not only a performing art, but also a charm of the nation's beauty and courage. Therefore, Debus is a martial art and brave at the same time. Therefore, the art is a wealth of Indonesian culture. The results show that the existence of debus to this day depends on its function, which continues to be strengthened, both within the debus method and outside the cultural system of the supporting community. Debus has undergone alternations to remain alive and attractive to today's society.